Surgical treatment of benign subungual tumours—a systematic review and case series - Pelicia Lim; Brian Yue; Andrew Cavallo (Australasian Journal of Plastic Surgery)
**Background**: Proper surgical technique is critical in the excision of benign subungual tumours to ensure complete tumour removal and prevent nail deformities. A systematic literature review was performed to identify approaches to excision and their clinical outcome. We present a series of rare benign subungual tumours to highlight different approaches and their outcomes. **Methods**: A systematic review of English language literature was conducted using the PubMed database between 1 January 1962 and 31 December 2021 for studies describing surgical approaches to benign subungual tumours. Search terms include ‘glomus tumour’, ‘subungual exostosis’, ‘osteoid osteoma’, ‘fibro-osseous pseudotumour of the digit’, ‘enchondroma’ and ‘implantation dermoid tumour’. We performed a retrospective review of patient records from our institute from 2021–2022. Six patients with subungual tumours were selected. **Results**: Twenty-one studies (with a total of 228 participants) described various techniques for excision of benign subungual tumours. The majority of the studies (n = 18) described the transungual approach, which allows maximum tumour exposure but with risk of nail deformity postoperatively. Other approaches described include lateral subperiosteal (n = 3), periungual (n = 2), nail bed margin (n = 1) and fish mouth (n = 2). Outcomes were measured using the rate of postoperative nail deformity and rate of tumour recurrence. Our series of patients were treated with excision using the transungual (5 of 6) and periungual approach (1 of 6), with good results. **Conclusion**: The available literature demonstrates that the transungual approach is the most widely used technique for removal of subungual tumours. This technique provides excellent tumour exposure; however, it is associated with damage to the nail bed. Our case series suggests that risk of nail dystrophy can be minimised by meticulous nail bed repair.